“Calm Down Dear, It’s Only a Simulator.” An investigation into the effects of the fMRI environment on cognition. - Black, Ashley Anne (My University, 2007)
Functional Magnetic Resonance Imaging (fMRI) is a useful tool which permits the observation of the brain’s neuronal activity in a non-invasive, on-line manner. The usefulness of the technique has however been questioned with some arguing, and going on to show, that the scanning environment itself can influence any cognitive function under investigation. The current study has been undertaken in order to specifically look at the influences of anxiety and claustrophobia on cognitive function in the fMRI environment. Participants completed an operation span task in 2 conditions (fMRI scanner simulator and normal laboratory setting) and mean performance levels between conditions were compared. It was found that performance on the task was significantly lower in the fMRI scanner simulator than in the normal laboratory setting. Anxiety and claustrophobia levels, measured using established scales, were correlated with performance in the scanner environment to investigate which, if any, were most related to performance in this unusual environment. State anxiety was found to be the only variable significantly related to performance in the fMRI scanner environment; it was shown that as state anxiety levels increased, performance in the scanner condition decreased. State anxiety was shown to predict a significant amount of the outcome variable, performance in the scanner environment. These results emphasise the key role state anxiety plays in causing reduced cognitive functioning in the fMRI environment. Such results also stress the need for something radical to be done to eliminate, or at least reduce, anxious reactions to the fMRI environment if we are to ever comprehensively study cognitive functioning using this technology.
Keywords: psychology